Gene Expression Profiling of Lacrimal Glands Identifies the Ectopic Expression of MHC II on Glandular Cells as a Presymptomatic Feature in a Mouse Model of Primary Sjögren's Syndrome - Yin, Junping; Zheng, Junfeng; Deng, Fengyuan; Zhao, Wenjie; Chen, Yan; Huang, Qiaoniang; Huang, Renliang; Wen, Lifang; Yue, Xiaoyang; Petersen, Frank; Yu, Xinhua (Frontiers in Immunology, 2018)
Ectopic expression of MHC II molecules on glandular cells is a feature of primary Sjögren’s syndrome (pSS). However, the cause of the ectopic expression of MHC II is unknown, and whether it play a role in the disease pathogenesis remain elusive. Here we report that ectopic expression of MHC II molecules on glandular cells was an early presymptomatic event in a mouse model for pSS induced by immunization of Ro60_316-335 peptide emulsified in Titermax as adjuvant. The ectopic expression of MHC II molecules was induced by Titermax but not complete freund's adjuvant (CFA). Furthermore, immunization of Ro60_316-335 peptide emulsified in Titermax, but not in CFA, could induce the pSS-like disease in mice. Therefore, this result suggests that ectopic expression of MHC II molecules on glandular cells is a presymptomatic feature of pSS, and such ectopic expression can be caused by environmental factors. In addition, this study also suggests a novel mechanism of adjuvant action in potentiating immune responses.